PENGARUH KEPEMIMPINAN KEPALA TAMAN KANAK-KANAK TERHADAP KINERJA GURU TAMAN KANAK-KANAK DI KECAMATAN AMALI KABUPATEN BONE - Sulastri, Eka; Marzuki, Kartini; Asri, Muhammad; Untung, Untung; Ridwan, Ridwan (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2025)
This research is quantitative research using descriptive methods which aims to determine the description of the leadership of school principals, the performance of kindergarten teachers and the influence of the leadership of kindergarten principals on the performance of kindergarten teachers in Amali District, Bone Regency. The independent variable in this research is leadership, while the dependent variable in this research is teacher performance. The population in this study was the entire kindergarten teaching staff in Amali subdistrict, Bone district, while the sample in this study was taken as a whole from the total population using a sampling technique, namely nonprobability sampling. The data analysis technique used is simple linear regression analysis. Based on the results of the descriptive analysis, it was found that the principal's leadership was classified as good with a percentage of 48.3% and teacher performance with a percentage of 43.3% was classified as very low. There is a positive influence between the leadership of kindergarten principals on the performance of kindergarten teachers in Amali District, Bone Regency. With a coefficient of determination value of 46.8% which is in the very low category, it can be concluded that teacher performance can run well even though the principal's leadership has not been optimal in carrying out its duties and functions, so the principal's leadership needs to be improved so that teacher performance is better.